Synthesis of new 3-cyanoacetamide pyrrole and 3-acetonitrile pyrrole derivatives. Issue 11 (16th March 2017) - Bayat, Mohammad; Nasri, Shima; Notash, Behrouz
Abstract: A new fused heterocyclic derivatives of pyrrole containing acetonitrile or cyanoacetonitrile moiety at 3-position is described by a one-pot multicomponent reaction. The reaction of dimedone, various aniline, aryl glyoxal with malononitrile/ethyl cyanoacetate/methyl cyanoacetate under mild conditions. The present method does not involve any hazardous organic solvents or catalysts. The significant features of this method are readily available starting materials, good yields, and easy purification. Graphical abstract: